Analysis of Growth Curve with Non-Linear Models of Gompertz and Logistics Model in Female Katjang X Boer Goats in Malaysia - Hifzan, R. M.; Mamat Hamidi, K.; Nur Aida, M. T.; Salisi, M. S. (Tropical Animal Science Journal, 2024)
This study aimed to predict the mature size specifically for body weight, body length, height at withers, and chest circumference in Katjang X Boer crossbred goats. The parameters of the growth curve, mature size (A), mature rate (k), and constant of integration (B) were estimated using Gompertz and Logistic non-linear growth models. A total of 228 heads of female Katjang X Boer goats were raised semi-intensively- weighed and measured monthly from birth to 54 months old. The coefficient of determination (R2) was used to find the ideal growth model to estimate growth curve parameters. Gompertz’s model demonstrated higher R2 values for body weight and height at withers (0.91, 0.99, respectively) than the logistic model (0.90, 0.97), while body length was comparable at 0.98. The Logistic model R2 for chest circumference was greater than the Gompertz model (0.98 vs. 0.96). Gompertz model estimated mature size (A) for body weight, height at withers, body length, and chest circumference were 37.68±1.63 kg, 60.40±0.57 cm, 53.83±0.73, and 70.62±0.89 cm, respectively while Logistic model estimated 36.27±1.42 kg, 60.05±0.54 cm, 53.65±0.71 cm, and 70.20±0.85 cm respectively. Parameters A and k had negative correlations from -0.439 to -0.530 (Gompertz) and -0.259 to -0.474 (Logistic), showing that animals with larger mature sizes tend to grow slower. The highest correlation coefficient between body sizes is body weight-chest circumference (0.961). Thus, the Gompertz model predicts body weight and height at withers better than the Logistic model, which is fitted for chest circumference. Both models are ideal for estimating body length.